MENGEKSPLORASI DAMPAK PEMBELAJARAN KOOPERATIF TIPE JIGSAW DENGAN GAYA MENGAJAR PRACTICAL WORK TERHADAP HASIL BELAJAR IPA KELAS VI SDN CITARIK III - Yuli Parlina; Supardi U S (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
Jigsaw-type cooperative learning is a learning process by dividing students into different groups, in order to discuss and solve problems. Meanwhile, the teaching style of practical work is the practical work of students in Learning in order to be able to understand science learning directly. As a commonly used teaching method and style, jigsaw-type cooperative learning and practical work teaching style are also often used by teachers in learning Natural Sciences (IPA), for example when learning the chapter on hot conduction of objects. While many other studies focus on teachers' teaching styles on other learning, this study examines the impact of jigsaw-type cooperative learning with practical work teaching styles on science learning outcomes of grade VI students. This study aims to explore the impact of the use of jigsaw-type methods and practical work teaching styles on students' science learning outcomes. This study uses a case study design. The data was then analyzed using observation and interviews. And in the conclusion, it was found that jigsaw-type cooperative learning and practical work teaching style had a positive impact on students' motivation and science learning outcomes. Therefore, jigsaw-type cooperative learning and practical work teaching style seem to be highly recommended to be applied in science learning.